The Old People in the Historical Sources from the 14th–16th Century Grand Duchy of Lithuania. Who Were They? - Čelkis, Tomas (Tautosakos darbai, 2024)
Various sources of the Grand Duchy of Lithuania (GDL) from the 14th–16th centuries quite frequently mention the old people. The author proposes a hypothesis that these individuals could have been connoisseurs and custodians of the customary law and the old tradition. They testified in the treaties between the GDL and the neighbouring countries, in which the borders of the states were determined, because, at that time, the “correct” borders were considered those that had been established for a long time, i. e. by the customs. These people tried to remember and indicate these borders. The old people used to participate in the GDL courts, in which issues of ownership, land boundaries, obligations, and evidence of the noble origins of the families were examined. Their primary task was to remember the “real” facts, i. e. the old ones. They did not attend the courts often, but, if necessary, the court officials would go and question them. Interestingly, the personal names of the old people who testified at courts were written down extremely rarely and for some reason these people usually remained anonymous. In addition, their age and the exact number of the old people who participated were rarely indicated. Some sources allow us assuming that in the courts, the old people were not only witnesses who remembered a lot and could speak about the past; they also represented the old customary law. At that time, the GDL courts were characterized by formalism, various customary rituals that distinguished between the examined events and emphasized their significance. Perhaps the old people observed what was said in the courts and how the other members of the community behaved, ensuring that things were done according to the established ancient norms. Thus, alongside the written law of the GDL, elements of the customary law also existed.
Keywords: Grand Duchy of Lithuania; old people; written law; customary law; state treaties